Acrokeratoelastoidosis in hansen's disease: A new insight - Vrutika Hasmukh Shah; Kinjal D Rambhia; Jayesh I Mukhi; Rajesh P Singh (Indian Journal of Dermatopathology and Diagnostic Dermatology, 2020)
Acrokeratoelastoidosis (AKE), first described by Costa in 1953, is characterized by small, firm, keratotic papules with central umbilication along the borders of the hands and feet. It is a type of palmoplantar marginal papular keratoderma and needs to be differentiated from other marginal papular keratodermas. AKE can be inherited or sporadic, with predisposing factors being excessive sun exposure, hyperhidrosis, and repetitive trauma. We here describe a case of AKE in a leprosy patient with probably secondary to repetitive chronic trauma due to loss of sensory function.